Knowledge and practices of supervisors on the performance management and development system at a primary health care facilities in the Greater Tzaneen Sub-district, Limpopo Province - Mashego, Rosemary Hlulekle (My University, 2016)
The South African government has introduced PMDS as a tool to monitor and manage the performances of departments, institutions, teams and individuals in order to improve service delivery, and to counteract the legacy of poor performance. In order for the government to achieve this goal, PMDS implementers must be equipped with adequate knowledge and skills which will enable them to implement the system correctly, in compliance with the standards and procedures laid down in the government PMDS policy. The aim of the study was to determine the knowledge and practices of PMDS of supervisors who are tasked with the responsibility to supervise their subordinates. Methods A cross sectional descriptive quantitative study was carried out in the Greater Tzaneen Primary Health Care facilities. A total of 117 participants comprising of professional nurses, operational managers and assistant managers completed the questionnaires. These comprised largely of close-ended questions and some open- ended questions. Analysis of data was done using statistical software, SPSS 22.0 version and results were interpreted. Results Generally all the respondents had average (65.8%) understanding of the PMDS processes including the purpose and their roles as supervisors. However, a gap exists between the theoretical knowledge and the actual ability to practise PMDS which was found to be around 52%. There are areas of weakness that still need attention: unavailability of PMDS guidelines, lack of training of both supervisors and employees. Lastly, the nature of challenges which the respondents reported regarding PMDS implementation signifies that there might be underlying problems with PMDS which were not covered by this study, and these challenges, by far outweigh their confident knowledge and ability to practise PMDS. v Conclusion To improve the knowledge and ability to supervise PMDS, the following recommendations were brought forth: proper induction of all PMDS supervisors and periodic in-service training, PMDS policy manuals as a source of reference to be made available in the facility and all supervisors to be orientated how to use them.
Thesis (MPH.) -- University of Limpopo, 2016.
Keywords: Performance management development system; Employees performance; Performance standards; Employees -- Rating of